Changes and Challenges of puberty in Adolescents with Autism Spectrum Disorder - Mohammed Akram Hamdan (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: The current study investigated the changes and challenges of puberty in adolescents with Autism spectrum disorder. Methods: The qualitative research methodology was used by conducting semi-structured in-depth interviews. The sample consisted of 12 parents (8 men and 4 women) whose adolescents have been diagnosed with Autism spectrum disorder from government or private clinics, and they (adolescents) were between 13-18 years old. Results: The findings indicate that most parents note that pubertal timing appears early in their children with Autism spectrum disorder, especially among female adolescents. Several parents indicate that some behaviors, such as stereotypical and repetitive behaviors decreased or stopped in their children during puberty. The findings of parents' responses analysis also show that their children experience several behavioral challenges during puberty, including anger, social withdrawal, sexual behaviors, daily life skills, menstruation, and eating. Conclusions: Puberty leads to significant unique challenges for individuals with Autism spectrum disorder. The impairment in communication skills and other behaviors associated with the disorder can lead to negative risks during this period. Different developmental challenges begin to appear in the behavioral, health, physical, and psychological aspects during puberty. The study recommends the need for counseling and training programs for children with Autism spectrum disorder and their parents to deal with the changes and challenges of puberty.